An LC–MS/MS method development and validation for the determination of clomiphene in biological matrices - Vinayaga Sundaram Krishnan, Bhikshapathi Darna (Journal of Applied Pharmaceutical Science, 2023)
A specific, linear, and precise liquid chromatography—tandem mass spectrometry procedure was established and subjected to the validation for the quantitation of clomiphene in plasma sample. YMC-Pack C18-AM (3μm; 4.6 mm i.d × 50 mm) stationary phase was utilized to achieve chromatography elution, through a flowing rate of 0.70 ml/minute. Isocratic elution was done using methanol, acetonitrile, and 0.10% V/V HCOOH in a fraction of 70:15:15 as the mobile phasic system. For clomiphene and nilotinib separation, liquid–liquid extraction method was carried out utilizing ethyl acetate as solvent. A triple quadrupole mass detector was employed for the quantification of ions. Electrospray ionization in a positive ionizing method, which was executed in multiple reaction monitoring with parent/product ionic transitions m/z 406.18→100.11 for clomiphene and 530.70→289.50 for nilotinib internal standard. A calibration graph was executed between the concentrations of 12.5–500.0 ng/ml and the resulting equation was y = 0.00413x – 0.00854 with an r2 value of more than 0.99. Clomiphene recovery values were found more than 95.82% and its accuracy measured in terms of relative error was in the range 3.25%–4.79%. Accuracy findings, sensitivity and recovery values of clomiphene in the sample plasma for the established technique evidences its importance in pharmacokinetic and bioequivalence study.
Keywords: LC–MS/MS, clomiphene, ovulation, validation, accuracy and linearity